2019
DOI: 10.1111/apt.15440
|View full text |Cite
|
Sign up to set email alerts
|

Development of a stratification tool to identify pancreatic intraductal papillary mucinous neoplasms at lowest risk of progression

Abstract: Summary Background Because most pancreatic intraductal papillary mucinous neoplasms (IPMNs) will never become malignant, currently advocated long‐term surveillance is low‐yield for most individuals. Aim To develop a score chart identifying IPMNs at lowest risk of developing worrisome features or high‐risk stigmata. Methods We combined prospectively maintained pancreatic cyst surveillance databases of three academic institutions. Patients were included if they had a presumed side‐branch IPMN, without worrisome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 57 publications
3
26
0
Order By: Relevance
“…11,12 Also, information on possible patient-related factors associated with progression risk is limited. 9,10 In addition to the limited knowledge of cyst and patient features, there are few available data on the role of genetic variants in this context. Because it has been reported that non-type O blood is associated with an increased risk of PDAC, 13,14 we hypothesized that this variant might also be associated with the risk of progression of BD-IPMN.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Also, information on possible patient-related factors associated with progression risk is limited. 9,10 In addition to the limited knowledge of cyst and patient features, there are few available data on the role of genetic variants in this context. Because it has been reported that non-type O blood is associated with an increased risk of PDAC, 13,14 we hypothesized that this variant might also be associated with the risk of progression of BD-IPMN.…”
Section: Introductionmentioning
confidence: 99%
“…Duration and intensity of surveillance differ between guidelines and are summarized in Table 4. Recent development of the Dutch American Risk Tool for IPMN (DART-I) allows more precise risk prediction for conversion to worrisome or high-risk features in BD-IPMN and may allow more conservativeor discontinuedsurveillance in low-risk IPMN [129]. Last years, there has been an increasing interest in artificial intelligence (AI)based diagnosis of IPMN and PCN in general.…”
Section: Surveillancementioning
confidence: 99%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article …”
Section: Acknowledgementsmentioning
confidence: 99%
“…We were pleased to read the editorial comments by Drs. Yang and Forsmark regarding our study describing the development of a stratification tool to identify low‐risk side branch intraductal papillary mucinous neoplasms (SB‐IPMN) . We thank them for commending us on our efforts, and for recognising the potential importance of developing a negative prediction tool to limit unnecessary procedures and to reduce the burden of surveillance on patients and the healthcare system.…”
mentioning
confidence: 99%